Development of High-Productivity Continuous Ethanol Production using PVA-Immobilized Zymomonas mobilis in an Immobilized-Cells Fermenter - Nurhayati, Nurhayati; Cheng, Chieh-Lun; Chang, Jo-Shu (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2014)
Ethanol as one of renewable energy was being considered an excellent alternative clean-burning fuel to replace gasoline. Continuous ethanol fermentation systems had offered important economic advantages compared to traditional systems. Fermentation rates were significantly improved, especially when continuous fermentation was integrated with cell immobilization techniques to enrich the cells concentration in fermentor. Growing cells of Zymomonas mobilis immobilized in polyvinyl alcohol (PVA) gel beads were employed in an immobilized-cells fermentor for continuous ethanol fermentation from glucose. The glucose loading, dilution rate, and cells loading were varied in order to determine which best condition employed in obtaining both high ethanol production and low residual glucose with high dilution rate. In this study, 20 g/L, 100 g/L, 125 g/L and 150 g/L of glucose concentration and 20% (w/v), 40% (w/v) and 50% (w/v) of cells loading were employed with range of dilution rate at 0.25 to 1 h-1. The most stable production was obtained for 25 days by employing 100 g/L of glucose loading. Meanwhile, the results also exhibited that 125 g/L of glucose loading as well as 40% (w/v) of cells loading yielded high ethanol concentration, high ethanol productivity, and acceptable residual glucose at 62.97 g/L, 15.74 g/L/h and 0.16 g/L, respectively. Furthermore, the dilution rate of 4 hour with 100 g/L and 40% (w/v) of glucose and cells loading was considered as the optimum condition with ethanol production, ethanol productivity and residual glucose obtained were 49.89 g/L, 12.47 g/L/h, and 2.04 g/L, respectively. This recent study investigated ethanol inhibition as well. The present research had proved that high sugar concentration was successfully converted to ethanol. These achieved results were promising for further study.